Use of otolith microchemical and morphological analyses for stock discrimination of Sarpa salpa on two Tunisian islands, Djerba and Kerkennah - Ben Ghorbel, Meriam; Mejri, Marwa; Adjibayo, Houeto Madel Floriane; Chalh, Abdellah; Quignard, Jean-Pierre; Trabelsi, Monia; Bouriga, Nawzet (Journal of the Marine Biological Association of the United Kingdom, 2024)
Otolith morphological and microchemical analyses are relatively new scientific research methods used in fish stock evaluation and management. However, in Tunisia, only morphological methods have been used. The objective of this study was the Sarpa salpa stock discrimination of Djerba and Kerkennah by the otoliths morphological and microchemical analysis, while carrying out a fluctuating asymmetry analysis and a stock comparison of males and females for each population. The results revealed significant differences between the Djerba and Kerkennah populations, significant differences between the stocks of males and females in each population, and a highly significant fluctuating asymmetry for both populations. The results of the otolith morphological analysis were similar to those of the microchemical analysis. This result proves that both morphological and microchemical analyses are powerful tools for fish stock discrimination.
Keywords: Biologie – Djerba

Dinoflagellates encystment with emphasis on blooms in Boughrara Lagoon (South-Western Mediterranean): Combined effects of trace metal concentration and environmental context - Abdmouleh Keskes, Fatma; Ayadi, Najla; Atoui, Abdelfattah; Mahfoudi, Mabrouka; Abdennadher, Moufida; Dammak Walha, Lamia; Ben Ismail, Sana; Ben Abdallah, Olfa; Khammeri, Yosra; Pagano, Marc; Hamza, Asma; Bel Hassen, Malika (Estuarine, Coastal and Shelf Science, 2020)
Keywords: Biologie – Djerba

Foraminiferal-based biotic indices to assess the ecological quality status of the Gulf of Gabes (Tunisia): Present limitations and future perspectives - El Kateb, Akram; Stalder, Claudio; Martínez-Colón, Michael; Mateu-Vicens, Guillem; Francescangeli, Fabio; Coletti, Giovanni; Stainbank, Stephanie; Spezzaferri, Silvia (Ecological Indicators, 2020)
Keywords: Biologie – Djerba